2021
DOI: 10.1007/s11356-021-13639-6
|View full text |Cite
|
Sign up to set email alerts
|

The roles of economic growth and health expenditure on CO2 emissions in selected Asian countries: a quantile regression model approach

Abstract: Continuous economic growth and the rise in energy consumption are linked with environmental pollution. Demand for health care expenditure increased after the COVID-19 pandemic. This study is interesting in modeling the nexus between public and private health expenditure, carbon dioxide emissions, and economic growth. To this end, the present study analyzed the nexus between public and private health care expenditure, economic growth, and environmental pollution for 36 Asian countries for the period 1991–2017. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
29
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(36 citation statements)
references
References 150 publications
(142 reference statements)
6
29
0
1
Order By: Relevance
“…They concluded and validate the EKC hypothesis in a specific group of countries. Using cross-section data set, research also supported similar results [7,18]. However, the recent investigations verified an EKC theory after examining crosssection data set in different countries.…”
Section: Review Of Literaturesupporting
confidence: 66%
“…They concluded and validate the EKC hypothesis in a specific group of countries. Using cross-section data set, research also supported similar results [7,18]. However, the recent investigations verified an EKC theory after examining crosssection data set in different countries.…”
Section: Review Of Literaturesupporting
confidence: 66%
“…They found that with the growing impact of renewable energy consumption, nearly half of the sample countries and two-thirds of the subsectors have experienced the transformation of the nexus between manufacturing growth and emissions. Bilgili et al [31] employed the panel quantile regression technique on a dataset from thirteen developed countries over the period 2003-2018 to find an inverted U-shaped nexus between economic growth and carbon emissions only in higher carbon-emitting countries, thus, confirming the EKC hypothesis. However, the U-shaped nexus is more predominant in lower carbon-emitting countries.…”
Section: Introductionmentioning
confidence: 92%
“…Many studies look for a one-way causal relationship between CO2 emissions and health expenditure and discover a positive correlation. However, only a few practical studies (Abdullah et al, 2016;Wang C.-M.et al, 2019;Bilgili et al, 2021) have focused on the two-way causal relationship between CO2 emissions and health expenditure, including some relevant and supported research on the relationship between CO2 emission and health expenditures. Greenhouse gas emissions raise health care expenses considerably, according to (Yahaya et al, 2016), who examined panel data from 125 countries (Metu et al, 2018); and (Abdullah et al, 2016) confirmed these results.…”
Section: Literature Reviewmentioning
confidence: 99%